Forest cover, use and dietary intake in the East Usambara Mountains, Tanzania - Powell, B.; Hall, J.; Johns, T. (2011)
Food insecurity and malnutrition in local populations both result from and drive deforestation. This paper examines the relationships between diet of local people and measures of forest cover and use in the East Usambara Mountains, Tanzania. Data on dietary diversity and intake were collected for 270 children and their mothers. Area of tree cover within the vicinity of each household was examined in relation to forest use and diet. Individuals using foods from forest and other non-farm land had higher dietary diversity, consumed more animal source foods and had more nutrient dense diets. They also had more tree cover in a close proximity to the home, suggesting a relationship between tree cover and forest food use. Households reporting trips to the forest had lower area of tree cover within close proximity, suggesting that land close to the home with tree cover such as agroforest and fallow is important for obtaining subsistence products. Although historically there has been little motivation for local people to participate in forest conservation in the East Usambaras, the maintenance of tree cover in the landscape around the home, especially on agricultural and village land, may be important in ensuring continued access to the health benefits potentially available in wild and forest foods.